KESADARAN ETIS DAN INTEGRITAS AKADEMIK MAHASISWA: SEBUAH KAJIAN KONSEPTUAL TENTANG TRANSFORMASI PERILAKU DI PENDIDIKAN TINGGI - Syafrizal; Mikyal Oktarina; Ilham Hidayatullah; Fitrah Nabila Dista; Nurliza Zuhra (CV. Gerasi Insan Nusantara, 2026)
Academic achievement has long been positioned as a primary indicator of success in higher education. However, an excessive orientation toward academic attainment risks obscuring the fundamental purpose of education, namely the formation of student integrity and moral responsibility. Academic realities reveal a growing misalignment between academic performance and ethical conduct, as reflected in various forms of academic dishonesty and the erosion of integrity within higher education institutions. This article aims to conceptually examine the role of ethical awareness as a driving force for the transformation of student behavior in the context of higher education. This study is constructed through a literature-based approach employing critical analysis of ethical theories, character education, and academic values relevant to contemporary higher education. The discussion emphasizes ethical awareness as an internalized moral consciousness that guides students in ethical decision-making, the internalization of academic honesty, and the integration of intellectual achievement with social responsibility. The article underscores the urgency of mainstreaming ethical awareness within curricula, pedagogical practices, and academic culture as a foundational framework for fostering sustainable student integrity. Accordingly, higher education is expected not only to produce academically accomplished graduates but also individuals who demonstrate strong character, integrity, and ethical sensitivity in both academic and social spheres